Development of Crack-Free Alumina Sol-gel/Poly(vinyl Alcohol) Membranes for Glucose Oxidase Immobilization - Wong, Fui Ling; Aziz, Azila Abdul (ASEAN Journal of Chemical Engineering, 2007)
A simple procedure to incorporate PVA into alumina sol-gel membrane was investigated as a suitable support material for glucose oxidase. The alumina sol was prepared using aluminum iso-propoxide via the sol-gel process. PVA was employed as the organic binder to enhance the mechanical strength of the fragile sol-gel membranes. The ability of the hybrid membrane to retain glucose oxidase and the apparent enzyme activities were studied. The resulting composite membranes were found to be crack-free, stable, and still very active after 60 days. However, the enzyme leakage period was observed to be quite long. The enzyme was still leaking from the membrane after more than 10 days albeit at a very low level.